The application of stable carbon and nitrogen isotopes to assess the feeding ecology of long-finned pilot whales (Globicephala melas) in Scotland - Anna Sophie Kebke; Tessa Plint; José Antonio Canseco; Nicholas J. Davison; Mariel T.I. ten Doeschate; Sascha K. Hooker; Clayton R. Magill; Silvia S. Monteiro; Rona McGill; Jason Newton; Clive Trueman; Andrew Brownlow (PLoS ONE, 2026)
Knowledge of the feeding habits of cetaceans is critical to the development of system-wide conservation strategies in marine ecosystems, yet dietary data are often lacking. To investigate the foraging ecology of long-finned pilot whales ( Globicephala melas ), we analysed stable carbon and nitrogen isotopes in skin tissue from 50 adult and juvenile animals that mass stranded in July 2023 on the Isle of Lewis, Scotland, in the Northeast Atlantic. We interpreted our isotope data with reference to published data from six delphinid species and baseline prey data from the region. We compared isotopic niche breadth among delphinid species and estimated dietary composition for long-finned pilot whales. The average isotopic values were —17.4 ± 0.9 ‰ for δ 13 C and +11.0 ± 0.7 ‰ for δ 15 N. The core isotopic niche of long-finned pilot whales overlapped with striped dolphin only, with a core niche overlap of 8.6%, suggesting some shared habitat and low trophic level prey, or foraging in habitats with lower baseline δ 15 N values. Adult male and female long-finned pilot whales showed complete isotopic niche overlap, although females displayed a wider niche. Estimated dietary contributions suggest a primarily benthopelagic foraging strategy linked to continental shelf edge and slope food webs. Our findings demonstrate the importance of deep-water prey resources to long-finned pilot whales, providing valuable insights into the early spring-summer feeding habits of the species and build baseline ecological data for the Northeast Atlantic. These results highlight the value of stable isotope analysis to advance our understanding of cetacean trophic ecology and better inform marine mammal conservation management.